Personal determinants of socio-comparative jealousy - Lepeshko, Kseniya V. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The problem of personal determination of socio-comparative jealousy is analysed. The individual-personal and cognitive-motivational characteristics-predictors determining the levels of significance of the situation of socio-comparative jealousy, cognitive and emotional socio-comparative jealousy, behavioural strategies of coping with the situation of socio-comparative jealousy are determined.
Keywords: socio-comparative jealousy; individual-personal and cognitive-motivational predictor characteristics